Involvement of the Actinobacillus pleuropneumoniae ompW Gene in Confrontation of Environmental Pressure - Chen, Xiabing; Shao, Zhiyong; Wu, Lijun; He, Bin; Yang, Wenhai; Chen, Jie; Jin, Erguang; Huang, Qi; Lei, Liancheng; Xu, Jiajia; Li, Haotian; Zhang, Hui; et al. (Frontiers in Veterinary Science, 2022)
Actinobacillus pleuropneumoniae causes porcine pleuropneumonia. The function of the outer membrane protein W gene (ompW) of A. pleuropneumoniae has not been evaluated. Thus a deletion mutant of ompW, ΔompW, was constructed to explore the effect of ompW gene deletion on bacterial growth, biofilm formation, bacterial morphology, oxidative tolerance, susceptibility to antibiotics, and the expression of ribosome synthesis and ABC transporter related genes. Results showed that the ompW gene deletion did not affect the growth of A. pleuropneumoniae but did affect biofilm formation, bacterial morphology during steady growth, oxidative tolerance, and bacterial susceptibility to polymyxin B, kanamycin, and penicillin. The ompW gene deletion also affected the expression of ribosome synthesis and ABC transporter related genes. These results suggested that ompW may regulate the biological phenotype of A. pleuropneumoniae.